A study to evaluate psychological and occlusal parameters in bruxism - Siddharth Bandodkar; Shuchi Tripathi; Pooran Chand; Saumyendra V. Singh; Deeksha Arya; Lakshya Kumar; Mayank Singh; Rameshwari Singhal; Adarsh Tripathi (Journal of Oral Biology and Craniofacial Research)
Purpose: To evaluate the role of anxiety/depression and occlusal factors in bruxism using Hospital Anxiety and Depression Scale and T-Scan III respectively. Methods: The present case control study was comprising of a group of thirty patients with bruxism (Group Br) and 30 healthy individuals as control group (Group NBr). Subjects were selected from outdoor patients visiting the dental unit with the chief complaint of wearing off/sensitivity of all the teeth due to habitual grinding. The cases were selected by using the diagnostic criteria as given by the American Academy of Sleep Medicine (AASM). Further based on similarities of age and gender, controls were selected. Tooth wear index was recorded using an index given by Ekfeldt et al. Hospital Anxiety and Depression Scale (HADS) questionnaire was administered to both the groups to evaluate anxiety and depression. Recording of occlusal parameters in both the groups was done digitally by using T-Scan III. Statistical analysis was done by using student's t-test, chi square test and Mann Whitney U test. Results: Group Br had significantly greater mean tooth wear index (22.24 ± 11.5) than group NBr (5.17 ± 3.30). Group Br had significantly higher anxiety (9.03 + 1.87/7.17 + 1.82) and depression scores (8 + 1.93/6.17 + 1.23) as compared to NBr. The disclusion time of group Br was 0.652 ± 0.749 and that of group NBr was 0.247 ± 0.289 (p = 0.008). Conclusions: Subjects with higher level of anxiety, depression and increased disclusion time may have greater predilection towards suffering from bruxism (p < 0.05).